Cultural and Linguistic Diversity in Recent Verbal Behavior Research on Individuals with Disabilities: a Review and Implications for Research and Practice - Brodhead, Matthew T. (Anal Verbal Behav, 2014)
The number of individuals from various culture and language backgrounds who are receiving behavior-analytic services is growing. Therefore, a behavioral understanding of the role of cultural and linguistic diversity (CLD) in language acquisition may be warranted. We searched recent editions of The Analysis of Verbal Behavior and the Journal of Applied Behavior Analysis to determine the degree to which researchers report the CLD of individuals with disabilities who participate in verbal behavior research. Our results indicate that researchers in these journals rarely report the culture and language background of their participants. Given these results, we provide a conceptual analysis and describe implications for research and clinical practice. A further understanding of the role of CLD may aid in the development of better behavioral interventions and culturally sensitive treatments. Finally, research that explores the role of CLD in language acquisition may add to the generality of behavior-analytic research and practice.